China's Dilemmas on the Road to Reforms Under Xi Jinping - Värk Juhan (Baltic Journal of European studies, 2015)
On 15 November 2012, at the plenary session of the Central Committee of the Communist Party of China, Xi Jinping was elected the Party' general secretary, whereas he also became the chairman of the influential Central Military Commission. Too eager to wait to be inaugurated as President of the People' Republic of China in March 2013, the new national leader announced that in the following decade he is guided by the main objective of his predecessor Hu Jintao to double the prosperity of the people by the year 2020 and to keep the country' economy stable and growing fast. Unfortunately, it will be difficult for the new leader of China to implement his intentions, since, presumably, the country' new leadership will be from the older generation, hardliners, and, most importantly, politically conservative. But the difficulties lie in carrying out economic reforms because of rampant corruption and shadow banking in the central apparatus and in regions.